Reliability-Based Forward Recursive Algorithms for Algebraic Soft-Decision Decoding of Reed--Solomon Codes - Haitao Xia; Cruz, J.R. (IEEE transactions on communications, 2007)
We propose efficient forward recursive algorithms for algebraic soft-decision list decoding of Reed-Solomon codes, which utilize channel reliability information, and outperform the Koetter-Vardy (KV) algorithm with lower decoding latency. We evaluate the performance of the proposed decoding algorithms on additive white Gaussian noise and partial response channels. Simulation results show that we can achieve better performance on a modified extended-extended partial response class 4 channel than on the best possible performance of the KV algorithm, as given by the asymptotic bound for high-rate codes.